2018
DOI: 10.1080/10942912.2018.1494196
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional value and flavor of turbot (Scophthalmus maximus) muscle as affected by cooking methods

Abstract: In this study, the effects of five cooking methods on nutritional value and flavor of turbot muscle were evaluated. Chemical compositions of samples were determined using AOAC methods, and the fatty-acid composition was determined by gas chromatography-mass spectrometry (GC-MS). Flavors of samples cooked using different methods were characterized by electronic nose. Volatile compounds were determined using solid-phase microextraction (SPME) followed by gas GC-MS. All the samples were investigated before/after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…Fish are important for human diet, being a good source of high-quality proteins, vitamins, and other essential nutrients, including n-3 polyunsaturated fatty acids (PUFAs) and trace minerals. Flatfish are a group of great commercial value, considered as low-fat fish (2–4% fat) with a firm, white, mild tasting flesh, highly accepted by the consumers (Cerdá and Manchado, 2013; Dong et al, 2018). The reduction of captures caused by fisheries’ exhaustion has promoted flatfish aquaculture mainly in Europe and Asia, with turbot and Japanese flounder Paralichthys olivaceus as the dominant species (Food and Agriculture Organization [FAO], 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Fish are important for human diet, being a good source of high-quality proteins, vitamins, and other essential nutrients, including n-3 polyunsaturated fatty acids (PUFAs) and trace minerals. Flatfish are a group of great commercial value, considered as low-fat fish (2–4% fat) with a firm, white, mild tasting flesh, highly accepted by the consumers (Cerdá and Manchado, 2013; Dong et al, 2018). The reduction of captures caused by fisheries’ exhaustion has promoted flatfish aquaculture mainly in Europe and Asia, with turbot and Japanese flounder Paralichthys olivaceus as the dominant species (Food and Agriculture Organization [FAO], 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Polyunsaturated fatty acids are known to be preferentially affected by oxidation during heating [96,97,98]. Thus, the degradation of LC-PUFAs in food during cooking and other culinary treatments has been reported by many authors [99,100,101,102,103,104,105,106,107,108,109,110,111]. However, other authors reported no decrease in EPA and DHA during cooking [70,83,112,113,114,115,116,117,118,119,120,121,122,123].…”
Section: Assumption 5: Culinary Treatments Decrease Epa and Dha Inmentioning
confidence: 99%
“…Thus, the nutritive value of products for human nutrition should be estimated on the basis of the contents of EPA and DHA, mg per g of product, which can be obtained using internal standards during chromatography, rather than levels, or the % of total FAs [83,117,127,134,135]. Furthermore, content estimates based on internal standards are scarce, and most data are published as the level, or %, of total FAs [100,101,102,105,106,107,108,109,110,111]. Here, we provide data obtained using internal standards, which allows us to compare the real nutritive value of fish and production animal products (Table 1).…”
Section: Assumption 5: Culinary Treatments Decrease Epa and Dha Inmentioning
confidence: 99%
“…For example, Dong et al . (2018) indicated that turbot muscle in microwave heating exhibited more abundant volatile compounds. And Chen et al .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, extensive research has shown that volatile compounds in cooked seafood were significantly influenced by cooking methods. For example, Dong et al (2018) indicated that turbot muscle in microwave heating exhibited more abundant volatile compounds. And Chen et al (2021) demonstrated that significant differences in aroma profiles have been found in tilapia muscles submitted to different thermal possessing (microwaving, roasting, steaming and boiling).…”
Section: Introductionmentioning
confidence: 99%